2001
DOI: 10.1111/j.1745-3984.2001.tb01124.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Omitted Responses on the Accuracy of Ability Estimation in Item Response Theory

Abstract: Practitioners typically face situations in which examinees have not responded to all test items. This study investigated the effect on an examinee's ability estimate when an examinee is presented an item, has ample time to answer, but decides not to respond to the item. Three approaches to ability estimation (biweight estimation, expected a posteriori, and maximum likelihood estimation) were examined. A Monte Carlo study was performed and the effect of different levels of omissions on the simulee's ability est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(96 citation statements)
references
References 12 publications
4
88
1
1
Order By: Relevance
“…Indeed, researchers have addressed specifically how one might handle missing item responses, and how missing data impacts parameter estimation in the item response context, as well as the estimation of statistics such as coefficient alpha (Finch, 2008;Enders, 2004;DeMars, 2002;De Ayala, Plake, & Impara, 2001;Mislevy & Wu, 1996, 1988Lord, 1983Lord, , 1974. These researchers found that estimation of both item response parameters and person ability parameters is compromised when missing data are treated as incorrect (Finch, 2008;DeMars, 2002;De Ayala, Plake, & Impara, 2001;Lord, 1974). Furthermore, even when missing data are treated as not reached, or left as missing, parameter estimation can be detrimentally impacted, particularly the standard errors of the estimates (Finch, 2008;DeMars, 2002).…”
Section: Methods For Dealing With Missing Datamentioning
confidence: 99%
“…Indeed, researchers have addressed specifically how one might handle missing item responses, and how missing data impacts parameter estimation in the item response context, as well as the estimation of statistics such as coefficient alpha (Finch, 2008;Enders, 2004;DeMars, 2002;De Ayala, Plake, & Impara, 2001;Mislevy & Wu, 1996, 1988Lord, 1983Lord, , 1974. These researchers found that estimation of both item response parameters and person ability parameters is compromised when missing data are treated as incorrect (Finch, 2008;DeMars, 2002;De Ayala, Plake, & Impara, 2001;Lord, 1974). Furthermore, even when missing data are treated as not reached, or left as missing, parameter estimation can be detrimentally impacted, particularly the standard errors of the estimates (Finch, 2008;DeMars, 2002).…”
Section: Methods For Dealing With Missing Datamentioning
confidence: 99%
“…In that case, the fact that the item response was missing had a direct relationship to the value that it would have been MNAR. MAR data were also simulated borrowing from approaches used in previous research (Finch, 2008;Enders, 2004;de Ayala, 2001). First, the number of correct item responses was calculated for each simulee across all items in the complete dataset.…”
Section: Methodsmentioning
confidence: 99%
“…Two types of missing data were simulated in the current study, MAR and MNAR. For MNAR data, the requisite proportion of missing values from the items were randomly selected from among those item responses that were simulated to be incorrect, using a method that is common in this literature (Andreis & Ferrari, 2012;Finch, 2008;de Ayala, 2001). This would correspond to the real world situation in which an individual did not respond to an item because the answer was unknown.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When this approach is not feasible, imputation of missing data appears as an advisable alternative. Imputation of missing data in IRT has been studied in the context of unidimensional models (Ayala, Plake, & Impara, 2001;DeMars, 2003;Finch, 2008Finch, , 2011Huisman & Molenaar, 2001;Sijtsma & Van der Ark, 2003). Recently, Wolkowitz and Skorupski (2013) proposed a single imputation approach intended to estimate statistical properties of items but not factor scores.…”
Section: * Introductionmentioning
confidence: 99%